Formulación de una propuesta de mejoramiento al proceso misional de producción de marcos para bicicleta de la Empresa metaltech – bicicletas Duarte LTDA. Bajo la Aplicación de las normas ISO 9001:2015 e ISO 14001:2015, en la ciudad de Bogotá. (2017)
All the companies of any productive sector, they must posses a structure and organization, which should help him to the fulfillment of aims, in routes to the constant improvent and to the risk evaluation in all the aspects and processses that are carried out inside her, at present not only it is important to have an influential and profitable company, but also there is important the implementation of quality standards that gives to the busiinessman an idea of development and of maintenance of the strcture organization.